Characterization and development of polycaprolactone (PCL)/montmorillonite (MMT)/hydroxapaptite (HA) nano-composites for fused deposition modelling (FDM) process - Abdul Haq, Raezul Haq (2015)
In this study, characterization and development of polymer nanocomposites filament wire for Fused Deposition Modelling (FDM) was investigated. The polycaprolactone (PCL) filled montmorillonite (MMT) and Hydroxyapaptite (HA) composites were prepared by melting and compounding using a single screw extruder. The mechanical properties were assessed by tensile, flexural and charpy impact tests while the thermal properties were studied via differential scanning calorimetry (DSC) and thermogravimetry analyzer (TGA). Simulated body fluid (SBF) test was used to assess the bioactivity properties of the composites. The filament wire with the diameter of 1.75+0.05 were fabricated using a single screw extruder with die hole 1.6 mm in diameter. Design of experiment (DOE) software was used to find the optimum setting for the screw speed, roller speed and die temperature in order to achieve the specific diameter of the filament wire. The flexural strength, elastic modulus and flexural modulus of PCL/MMT blends increased with the decrement of tensile strength and impact strength. Apparently, the inclusion of HA upon PCL/ MMT composite shows a slight improvement in elastic modulus, flexural modulus and flexural strength with reduction of impact strength. Addition of MMT and HA enhanced the thermal stability and the decomposition temperature of the composites. Formation of apatite crystals on the PCL/MMT/HA composites surfaces confirmed the occurrence of bioactive properties. Composites with 3 wt.% of MMT and 10 wt.% of HA were chosen as optimum composition in terms of strength and bioactive properties to be fabricated as filament wire for FDM process. The optimum parameter setting to produce 1.75+0.05 of filament wire was successfully found at screw speed of 7.30 Hz, roller speed of 4.3 rpm and die temperature of 90°C. The characteristic of the FDM process shows that the samples with optimum dimensional accuracy and relative density was found at room temperature and 80°C of platform and nozzle temperature respectively. The composites with 3 wt.% of MMT and 10 wt.% of HA samples produced from the FDM process show an improvement in elastic modulus and impact strength compared to samples prepared by injection molding process.